ITALIANS IN LONDON - Sacco, Giuseppina (European Scientific Journal, ESJ, 2013)
The present research on migration to London is part of a larger project involving other similar investigations dealing with the Americas (specifically Canada and Argentina). The purpose of the overall project is the systematic study of some socio-demographic variables and the most significant factors that have helped shape the evolution of international migration in a settlement today. It also illuminates, in a diachronic development, a possible link between the determinants of European and transoceanic migrations and suggests the likely differences. The results that will be presented in this paper are those of the study of a sample obtained by a non-probability snowball sampling through interviews with 221 Italian immigrants in London. The data retrieval is achieved by administering a pre-structured questionnaire. The survey method was based on the traditional and effective optical gender related to different demographic, social and economic factors in order to find different aspects of Italian regional migration to London. We have seen that gender difference has increasingly become more helpful in modifying the traditional migration profiles of Italian regions.